A review of the genus Capulinia Signoret (Hemiptera: Coccoidea: Eriococcidae) with description of two new species - Kondo, T.; Gullan, P.j.; Cook, L.g. (Zootaxa, 2016)
The eriococcid genus Capulinia Signoret currently comprises four Neotropical species (the type species C. sallei Signoret, C. crateraformis Hempel, C. jaboticabae Ihering and an undescribed species recognised in the literature) and one species from New Zealand (C. orbiculata Hoy). All species feed on plants in the family Myrtaceae and the undescribed species is a pest of guava, Psidium guajava, in Venezuela and Colombia. Here we describe the pest species based on the adult female and first-instar nymph and name it Capulinia linarosae Kondo & Gullan sp. n. We provide a summary of published information on the biology and pest status of C. linarosae by translating the Spanish literature. We also describe the adult female and first-instar nymph of a new Argentine species that we name as C. luma Kondo & Gullan sp. n. after its host Luma apiculata. In addition, we redescribe the adult female of C. jaboticabae and include notes on C. crateraformis, C. orbiculata and C. sallei. We provide a revised generic diagnosis and keys to all Capulinia species based on adult females and, where available, first-instar nymphs, as well as a revised key to South American eriococcid genera. Phylogenetic analyses of 18S rDNA place Capulinia within the "Gondwanan" clade of eriococcids, mostly likely within the Myrtaceae-feeding group.